Pengaruh Pengendalian Internal Persediaan Terhadap Efektivitas Pengelolaan Persediaan Barang Dagang - Mahazaki, Muhammad; Robinson (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
One of the problems faced by UMKM in Bengkulu City is that there are still poor quality and damaged commercial goods. This is due to the lack of control and inspection of merchandise received from factories and customer returns. This study aims to determine the effect of internal control of supplies on the effectiveness of trade inventory management in UMKM in Bengkulu City. This study uses a simple linear regression analysis method using SPSS version 26. Data collection techniques are obtained from primary data using purposive sampling method by distributing questionnaires. The result of this study is a correlation coefficient of 0.420 which shows that the relationship between independent and dependent variables is classified in the medium category, the magnitude of influence between internal control of inventory on the effectiveness of trade inventory management in UMKM in Bengkulu City is 17.6%. The results offer hypothesis test show that internal control of inventory has a significant influence on the effectiveness of trade inventory management in UMKM in Bengkulu City.